Colour preference between adults and children during a dental treatment session - KAZAK, MAĞRUR; Ozdas, Didem Oner; KAZAK, MAĞRUR (My University, 2017)
Background: It is evidently shown that colour has physical, psychological and sociological effects on human beings. There are many studies showing the effects of colours on brain activity. Colour preferences may change from childhood to adulthood and are significantly different in various age groups. The aim of this study was to evaluate the adults and children in their preference for mouthrinses in various colours under stress condition during a dental treatment session.